Determining Climatic Stable Areas of Kerman, applying Statistical Multivariable Methods - Kamal Omidvar; Marzieh Shamsodini Fard (جغرافیا و پایداری محیط)
It is obvious that the Recognition of climatic features of each region can play an important role in land use and planning. It is necessary to determine climatic stable areas precisely in order to get sustainable development. One of the new methods determining climatic stable areas is statistical multivariable methods such as factor analysis and cluster analysis using Geographical Information System (GIS). Considering the vastness of Kerman province, there are many climatic diversities in this province. In the present research, statistical methods like factor analysis and cluster analysis using GIS were applied to identify climatic stable areas in the aforesaid region. Therefore, 36 climatic variables were selected from 12 meteorology stations during a statistical 30 -years period (1979-2008). Consistent with the distance of stations and positional variations of the selected variables, a network in 15×15 km dimensions was developed over Kerman province. The values of 36 variables were estimated using Kriging method. Factor analysis method accompanied by varimax (vertical) rotation were used to reduce data matrix dimensions, while cluster analysis method was used to determine the climatic stable areas. Moreover, the related maps were drawn applying GIS. The findings revealed that the climate of Kerman province is consisted of four factors called temperature, precipitation, humidity and wind, respectively, which include 90.77 percent variance of primary variables. The most outstanding climatic feature of southern areas is heat, while in mountainous area is precipitation, in Jiroft and Kanouj areas is humidity and in dry areas is wind. The presence of six climatic stable areas is specified in this province using cluster analysis performed on four factors and based on factor scores.